Neoliberalismo e dependência na América Latina. - Soares Campos, Rosana; Campos, Christiane (Espacio Abierto, 2014)
Â The objective of this study is to show how and why Latin America was becoming a region conducive to neoliberalism, by analyzing the type of development project in the region and the assumption that the implementation of neoliberal economic policies was “facilitated” by democratically elected governments. A historical economic analysis was made using statistical data for the 1960 to 1990 period. It can be seen that the social maladjustment in the 1990s was the result of the tripod: dependent development, policy choices and neoliberalism.